Actuarial Reserve for Accumulated Leave Benefits(GCR)with Enhanced Mortality and Interest Rate Modeling - Nur Idayu Ah Khaliludin; Haslinawati Mohd Mustapha; Nor Aziyatul Izni; Nur Ilyana Ismarau Tajuddin; Muhammad Nuruddin Sudin (Usim Press, 2026)
Indexed by MyCite